Nasionalisme Dan Cinta Tanah Air - Fensy Afri Utami; Putri Nur Qolbiyah; Fariza Arsyiandana (JPT : Jurnal Pendidikan Tematik, 2025)
Nationalism is a sense of love and pride in our own homeland and also our awareness of a shared identity as Indonesian citizens who have the same goals. Nationalism and love for the homeland are fundamental concepts that form the basis of the unity and integrity of the Indonesian nation. These values ​​are very important to be instilled from an early age through formal education and the family environment. With the love of the homeland that is instilled in children through activities such as ceremonies every Monday by respecting the red and white flag, singing the song Indonesia Raya, and reciting Pancasila. Other activities, for example, commemorate national holidays with competitions or cultural performances, introduce various national cultures in a simple way by showing miniature temples and telling about the history of the temple, through a comprehensive understanding, it is hoped that the young generation of the nation can foster strong nationalism based on the noble values ​​of the nation and religious teachings, so that they are able to play an active role in maintaining national unity amidst the challenges of rapid globalization today.